If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -17.3 + -1m = 22.8 Solving -17.3 + -1m = 22.8 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '17.3' to each side of the equation. -17.3 + 17.3 + -1m = 22.8 + 17.3 Combine like terms: -17.3 + 17.3 = 0.0 0.0 + -1m = 22.8 + 17.3 -1m = 22.8 + 17.3 Combine like terms: 22.8 + 17.3 = 40.1 -1m = 40.1 Divide each side by '-1'. m = -40.1 Simplifying m = -40.1
| 5+30=x+6 | | 2xy+10=90 | | x^9=-7 | | 3x+39=0 | | 3i*3i= | | -0.9(7.5w-6)-9= | | i*3i= | | 9(x-4)+x=10(x-4)+4 | | .02=15.4 | | -5x+3.6=2.1-4x | | 7.5(-0.9w-9)-6= | | x^2+2=3y | | 3x^3+5x-24=0 | | 4x+8x=2(6x-12) | | 4(8-5x)=25 | | -8+22=15x-2-14x | | (8a-5x)2= | | x-6=-2-24 | | -47.62=k+89.2 | | 2x^2+22x+54=0 | | (7+3y)2= | | 6x=3(2x+5) | | 180k^2+300k+125=0 | | 6m-(31m-18)=12(m-1)+3m | | y=8-(1/2)x | | 160x^2-250=0 | | -3c^2+4c-4= | | h=25433(9.5)+28.465 | | 6x+8-4x=20 | | 4(k-2)-6=3k-(2k-3) | | m+m+18=31 | | 243g^2+54g+3=0 |